2012
DOI: 10.1007/s11904-012-0133-9
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances (2011-2012) in Technology-Delivered Interventions for People Living with HIV

Abstract: Technology is rapidly advancing and becoming a cost effective option for intervention delivery particularly for isolated and hard to reach populations, such as people living with HIV/AIDS. A systematic review was conducted to identify recent technology based interventions for people living with HIV. The review yielded 12 studies that were grouped by the health behavior that it addressed and then the type of technology utilized. The majority of studies reviewed focused on medication adherence and used several d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(65 citation statements)
references
References 41 publications
1
64
0
Order By: Relevance
“…Mobile and or electronic health technologies represent a viable option to deliver behavioral interventions targeting ART adherence [17, 24] and also to reach, engage and retain young adults in HIV prevention and care [25]. Reported benefits include a more efficient use of provider resources, increased reach for hard to access populations [26], and potential to mitigate barriers, including travel to healthcare settings [27].…”
Section: Introductionmentioning
confidence: 99%
“…Mobile and or electronic health technologies represent a viable option to deliver behavioral interventions targeting ART adherence [17, 24] and also to reach, engage and retain young adults in HIV prevention and care [25]. Reported benefits include a more efficient use of provider resources, increased reach for hard to access populations [26], and potential to mitigate barriers, including travel to healthcare settings [27].…”
Section: Introductionmentioning
confidence: 99%
“…In another systematic review on the use of health tools for PLWH, all of the US studies in the review focused on the use of mobile technology as a data collection tool for targeting smoking cessation in PLWH [18]. A recent review of 12 technology-based interventions for PLWH in the US and abroad identified several gaps in content including sexual risk reduction, engagement, and retention in care [19]. Currently there are many mHealth apps for PLWH [20] but few have been developed by using information gathered from potential app users or healthcare providers.…”
Section: Introductionmentioning
confidence: 99%
“…To date, the focus of most evidence-based HIV behavioral interventions for people living with HIV (PLWH) has been rather narrow, targeting risk reduction for HIV and sexually transmitted disease reinfection or medication adherence (Centers for Disease Control and Prevention [CDC], 2013a; Pellowski & Kalichman, 2012). These interventions fail to address the multiple dimensions of self-management, including adherence to routine medical visits, healthy dietary intake, exercise regimes, self-monitoring of health status, and/or stress reduction.…”
Section: Background and Significancementioning
confidence: 99%